Hubungan Antara Penyesuaian Sosial Dengan Konformitas Siswa SMP - Triasih, Yuda Joko; Tagela, Umbu; Windrawanto, Yustinus (Universitas Muria Kudus, 2023)
This study aims to determine the significance of the relationship between social adjustment and conformity in class IX students of SMP Negeri 1 Suruh for the 2022/2023 Academic Year. The research method used is a descriptive approach with a correlational research type. The population in this study were 281 students with a total sample of 162 students who were taken using a proportional random sampling technique. The results of the descriptive analysis of the research show that the variables of social adjustment and student conformity are in the moderate category with a percentage of 48%. Correlation analysis in this study used Kendall's tau-b technique with the results showing that there was a significant relationship between social adjustment and conformity in class IX students at SMP Negeri 1 Suruh.